2009
DOI: 10.1016/j.febslet.2009.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Human cytosolic tRNase ZL can downregulate gene expression through miRNA

Abstract: Edited by Tamas Dalmay Keywords:A long form of tRNase Z TRUE gene silencing Small guide RNA MicroRNA Non-coding RNA RNA-induced silencing complex a b s t r a c t A long form of tRNase Z (tRNase Z L ) can cleave any target RNA at any desired site under the direction of artificial small guide RNA including $25-nucleotide hook-shaped RNA. Here we show that human miR-103 can form a hook structure to guide target RNA cleavage by human cytosolic tRNase Z L in vitro. In vivo analyses using luciferase mRNAs modified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Importantly, these RNAs appear to play key roles in the progression of the cell cycle (Haussecker et al, 2010; Lee et al, 2009). Other evidence directly links the processing of tRNA by RNaseZ L to result in RNaseZ L mediated cleavage of the target mRNA using processed tRNA fragments (Elbarbary et al, 2009a, 2009b). Initially, it was shown that pol III transcription of tRNA stemloop constructs could generate synthetic siRNAs to target a gene of interest and processing of the siRNA was hypothesized to use the RNaseZ L tRNA processing enzyme (Scherer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these RNAs appear to play key roles in the progression of the cell cycle (Haussecker et al, 2010; Lee et al, 2009). Other evidence directly links the processing of tRNA by RNaseZ L to result in RNaseZ L mediated cleavage of the target mRNA using processed tRNA fragments (Elbarbary et al, 2009a, 2009b). Initially, it was shown that pol III transcription of tRNA stemloop constructs could generate synthetic siRNAs to target a gene of interest and processing of the siRNA was hypothesized to use the RNaseZ L tRNA processing enzyme (Scherer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological significance remains to be completely elucidated, recent experimental evidence suggested that small RNAs derived from rRNA (srRNAs) and tRNA (tsRNAs) are able to modulate gene expression in response to certain survival pressures [9,10,20,26,27,29,38].…”
Section: Q2mentioning
confidence: 99%
“…Some reports suggest a connection between miRNA-and small tRNA-mediated pathways after demonstrating that human cytosolic tRNase Z can downregulate gene expression by using miRNAs as guides (70).…”
Section: More Small Rna Regulatory Pathways In Sight Do They Have a mentioning
confidence: 99%